Tussilagone Inhibits Osteoclastogenesis and Periprosthetic Osteolysis by Suppressing the NF-κB and P38 MAPK Signaling Pathways - Hu, Xuantao; Yin, Ziqing; Chen, Xia; Jiang, Guangyao; Yang, Daishui; Cao, Ziqin; Li, Shuai; Liu, Zicheng; Peng, Dan; Dou, Pengcheng (Frontiers in Pharmacology, 2020)
Backgroud: Aseptic prosthetic loosening is one of main factor producing poor prognosis of limb function after joint replacement and requiring troublesome revision surgery. It is featured by wear particle–induced periprosthetic osteolysis mediated by excessive osteoclasts activated in inflammatory cell context. In our previous study, some natural compounds showing anti-osteoclast trait with high cost-efficiency and few side effects. Tussilagone (TUS), as the main functional extract from Tussilago Farfara precedently used for relieving cough, asthma and eliminating phlegm in traditional medicine, has been proved to appease several RAW264.7-mediated inflammatory diseases via suppressing osteoclast-related signaling cascades. However, whether and how TUS can improve aseptic prosthetic loosening via modulating osteoclast-mediated bone resorption still need to be answered. Methods: We established a murine calvarial osteolysis model to detect the preventative effect of TUS on osteolysis in vivo. Micro-CT scanning and histomorphometric analysis were used to determine the variation of bone resorption and osteoclastogenesis in samples. The anti-osteoclast-differentiation and anti-bone-resorption bioactivities of TUS in vitro were investigated using bone slice resorption pit evaluation and interference caused by cytotoxicity of TUS was excluded according to CCK-8 assay. Quantitative PCR analysis was applied to prove the decreased expression of osteoclast-specific genes after TUS treatment. The inhibition effect of TUS on NF-κb and p38 MAPK signaling pathways was testified by western blotting and NF-κB-linked luciferase reporter gene assay. Results: TUS demonstrated bone protective effect against osteolysis in murine calvarial osteolysis model with reduced osteoclasts compared to the control group. Following studies in vitro witnessed that TUS exert anti-osteoclastogenesis and anti-bone-resorption effects in both BMMs and RAW264.7 cells, as evidenced by the decline of osteoclast specific genes according to quantative PCR. Western blotting revealed that TUS-treated demonstrated inhibited IκBα degradation and p38 phosphorylation.